Objective Evaluation Criteria for the Safety Certification of Autonomous Navigation System (London Journal of Engineering Research, 2026)
In Japan, the commercialization of the autonomous ship is aiming at the full-scale commercial operation around 2030 with the cooperation of industry, academia and government. The autonomous navigation system that the ships will be equipped with is one of the main functions of the autonomous ship. Commercialized autonomous ships coming soon are scheduled to operate on domestic routes. In areas covered by the Collision avoidance Regulations (COLREGs), autonomous ships will basically navigate without human intervention, including in congested waters. The Japan Captains’ Association believes that ships equipped with such autonomous navigation systems must have the same safety level as conventional ships and comply with the COLREGs. In other words, the autonomous ship should not cause anxiety to encountering ships. Based on the above basic policy, the Japan Captains’ Association and ClassNK conducted a large-scale verification experiment aimed at formulating standards for classification companies to objectively evaluate the safety of autonomous navigation systems and developed evaluation area diagrams for certification. This paper introduces the evaluation area diagrams that objectively evaluates autonomous navigation systems to have the same or higher safety level as conventional ships and to objectively evaluate compliance with COLREGs. In the evaluation area diagram, “Safety area”, “Caution area”, and “Danger area” are calculated based on the relative distance and bearing (compass bearing) change rate etc, between the autonomous ship and the encountered ships. When a ship using an autonomous navigation system navigates in a way that avoids entering “Caution area” and “Danger area”, it can be said that the ship is reducing risk before there is a risk of collision.ClassNK will use the evaluation area diagram introduced here to carry out certification work for the autonomous navigation system which will undergo demonstration experiments in 2025.This paper also discusses how to objectively explain compliance with the COLREGs, which contains many ambiguous expressions.